Temporal and sequential changes of glial cells and cytokine expression during neuronal degeneration after transient global ischemia in rats - Tsuchihashi Y (Journal of Neuroinflammation, 2011)
Abstract Background How glial cells and cytokines are associated with the progression of delayed neuronal death induced by transient global ischemia is still unclear. To further clarify this point, we studied morphological changes in glial cells (microglial cells and astrocytes), and cytokine protein levels, during the progression of neuronal cell loss in CA1 (Cornu Ammonis 1) of the hippocampus after transient global ischemia. Methods Morphological changes in glial cells were studied immuno-histochemically. Nine cytokines (IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, GM-CSF, IFN-γ and TNF-α) were simultaneously measured by a multiplexed bead-based immunoassay from 6 h to day21 after transient four vessel occlusion (4VO) in rats. Results During the process of neuronal loss, we observed four distinct phases: (1) lag phase day0-2 (no NeuN+ cell loss observed), (2) exponential phase day2-7 (NeuN+ cells reduced in number exponentially), (3) deceleration phase day7-14 (reduction rate of NeuN+ cells became low), (4) stationary phase day14 onward (NeuN+ cell loss progressed no longer). In the lag phase, activated glial cells were observed in the entire hippocampus but later were gradually restricted to CA1. Cytokine protein levels in the lag and exponential phases were lower than in the deceleration and stationary phases. IL-1α, IL-1β, IL-4, IL-6 and IFN-γ in 4VO were significantly higher in all four phases than in sham. Compared with sham level, GM-CSF was significantly high in the deceleration phase. TNF-α was significantly high in both the deceleration and stationary phases. Conclusion Ischemic stress in 4VO activated glial cells in areas beyond CA1 in the lag phase. Pyramidal neurons were injured in CA1 from the end of the lag phase and then neuronal cells reduced in CA1 in the exponential phase. After neuronal death began, the influence of dead cells on glial cells and cytokine expression gradually became stronger than the influence by ischemic stress. Therefore, from the deceleration phase, changes in glial cells and cytokine production were likely caused by dead cells. Cytokine interaction in the microenvironment may determine the functions of IL-1α, IL-1β, IL-4, IL-6 and IFN-γ in all four phases. The function of GM-CSF and TNF-α in the deceleration phase may be neurotrophic.